2023
DOI: 10.3390/ijms24032648
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of Small Molecule COX-1 and Akt Inhibitors as Anti-NSCLC Agents Endowed with Anti-Inflammatory Action

Abstract: Targeted therapies have come into prominence in the ongoing battle against non-small cell lung cancer (NSCLC) because of the shortcomings of traditional chemotherapy. In this context, indole-based small molecules, which were synthesized efficiently, were subjected to an in vitro colorimetric assay to evaluate their cyclooxygenase (COX) inhibitory profiles. Compounds 3b and 4a were found to be the most selective COX-1 inhibitors in this series with IC50 values of 8.90 µM and 10.00 µM, respectively. In vitro and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 90 publications
0
7
0
Order By: Relevance
“…27 The presence of hydrazide-hydrazone linkers have also shown anti-cancer activity against non-small cell lung cancer cell lines (NSCLC's). 28–30…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…27 The presence of hydrazide-hydrazone linkers have also shown anti-cancer activity against non-small cell lung cancer cell lines (NSCLC's). 28–30…”
Section: Introductionmentioning
confidence: 99%
“…27 The presence of hydrazide-hydrazone linkers have also shown anti-cancer activity against non-small cell lung cancer cell lines (NSCLC's). [28][29][30] Quinolines are well known for their antimalarial nature and recently their uses have extended further into the disciplines of anti-diabetic agents, 31 anti-cancer therapeutics, 32,33 neurodegenerative diseases 34 etc. The quinoline base exhibits strong binding with various apoptotic proteins, thereby making the heterocycle a good starting point for anti-cancer drug design strategies.…”
Section: Introductionmentioning
confidence: 99%
“…14−18 Hydrazones have been reported to exert striking antitumor action via induction of apoptosis, cell cycle arrest, inhibition of angiogenesis, and a plethora of cancer-related biological targets (e.g., Akt). 19 Benzoxazoles are privileged building blocks for the synthesis of biologically active ligands targeting a plethora of crucial targets/pathways due to their unique features allowing them to effectively bind to diverse biological targets with distinct affinities. 27−31 Several studies have revealed that benzoxazoles exert marked cytotoxic activity against a variety of cancer cell lines through diverse mechanisms including induction of apoptosis, inhibition of Akt phosphorylation, and so on.…”
Section: Introductionmentioning
confidence: 99%
“…The publications related to hydrazones and benzoxazoles exerting pronounced anticancer activity through inhibition of target enzymes involved in the pathogenesis of lung cancer motivated us to design novel anti-NSCLC agents by means of the molecular hybridization of the benzoxazole core with the hydrazide group, which was conjugated with the benzylidene moiety substituted at the para position with dialkylamino groups (dimethylamino, diethylamino), nitrogen-containing electron-withdrawing groups (nitro substituent), five- (pyrrolidine) or six-membered heterocyclic motifs (piperidine, morpholine and piperazine), heteroaromatic rings (imidazole, triazole) based on our previous work (Figure ), and the structure–activity relationships of existing Akt inhibitors together with the bioisosteric replacement. In this context, the designed compounds were synthesized readily and assessed for their cytotoxic properties on human lung adenocarcinoma (A549) and mouse embryonic fibroblast (L929) cells.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation